2020
DOI: 10.4103/jfmpc.jfmpc_342_20
|View full text |Cite
|
Sign up to set email alerts
|

Postendodontic pain in asymptomatic necrotic teeth prepared with different rotary instrumentation techniques

Abstract: Objectives: to investigate the postendodontic pain in asymptomatic necrotic teeth prepared with different rotary instrumentation techniques after single-visit root canal treatment. Materials and Methods: A total of 60 single-rooted teeth with single root canal were treated endodontically. Teeth were divided randomly into four equaled groups ( n = 15) according to instrumentation systems as follows: group I were shaped using ProTaper Universal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the current study Xp endoshaper resulted in less postoperative pain than the Oneshape file. Some studies 11,12,32 stated that XP endoshaper caused less postoperative pain when compared to other files, which is in agreement with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study Xp endoshaper resulted in less postoperative pain than the Oneshape file. Some studies 11,12,32 stated that XP endoshaper caused less postoperative pain when compared to other files, which is in agreement with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…27,28 The results of our study show that the mean pain values were the highest at 6 h after endodontic treatment and gradually decreased over 72 h. This may be due to the irritation of the periapical area caused by the extrusion of instrumentation debris, leading to local inflammatory reactions and subsequent pain. The pain typically subsides after the healing of the periapical area at 72 h. 5 This study found statistically significant differences in post-endodontic pain between the tested instrumentation techniques at 6, 12, 18, 24, 48, and 72 h. The XPS group had the lowest VAS pain values and the lowest amount of extruded debris, with the result being similar to that reported by Uslu et al 29 There were no statistically significant differences between the HEDM and WOG techniques. Similarly, Fontana et al 6 and Yeter et al 30 found that HEDM and WOG were comparable in terms of the amount of extruded debris.…”
Section: Discussionmentioning
confidence: 99%
“…4 Apical debris extrusion is believed to induce acute inflammatory reactions and is considered a direct cause of post-endodontic pain. 5,6 Nowadays, numerous rotary instruments have been developed with advanced metallurgy and mechanisms to facilitate endodontic treatment. Nonetheless, all preparation instruments and techniques are still associated with some degree of debris extrusion, which may cause postendodontic pain.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with previous studies that have reported that the post-operative pain level was higher when hand files were used compared to the use of multi-file rotary file systems of tapers ranging from 0.04–0.06. Single-file reciprocal systems were also reported to have higher post-operative pain levels than multi-file rotary file systems [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that SAF [ 20 , 30 ] and XP-endo shaper [ 27 , 28 ] induced decreased post-operative pain when applied alone for root canal instrumentation. When the XP-endo finisher [ 31 ] was used as supplemental instrumentation, it caused less post-operative pain.…”
Section: Discussionmentioning
confidence: 99%